Unraveling the spectrum: overlap, distinctions, and nuances of ADHD and ASD in children - Martinez, Sabrina; Stoyanov, Kalin; Carcache, Luis (Frontiers in Psychiatry, 2024)
This review explores the clinical presentation of similarities and differences in Attention-Deficit/Hyperactivity Disorder (ADHD) and Autism Spectrum Disorder (ASD). This paper investigates the deficits in executive function, social function, and emotional intelligence that are seen in both conditions and how the presence of both conditions can exacerbate these deficiencies. Understanding the clinical presentations in these domains is critical to refine diagnostic methods and treatments and improve outcomes for those affected by these neurodevelopmental disorders. The similarities in clinical presentation between ADHD and ASD present a significant diagnostic challenge, with individuals often exhibiting similar behaviors and difficulty navigating the complexities that encompass reacting to their environment. Further research is paramount in gaining more knowledge of the disorders and challenges faced by these individuals, especially those with the presence of both conditions.